Análise das características clínica, histopatológica e imunopatológica das lesões liquenoides orais. Revisão sistemática e estudo prospectivo - Ferrisse, Túlio Morandin [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The concept of lichenoid reaction or lichenoid interface was introduced in dermatology to define various inflammatory diseases of the skin that have similar histopathological features. Just as the skin and oral mucosa is affected by a variety of oral lichenoid lesions (OLLs). OLLs were classified as contact Lichenoides injury; drug Lichenoides injury; chronic graft versus host and not classifiable lichenoid lesions aspect lichen planus-like, such as chronic ulcerative stomatitis (CUS) recently described. Besides the overlapping features among injuries that make up this group, oral lichen planus (OLP) is the main differential diagnosis. Traditionally, the diagnosis of OLLs and the OLP depends on the clinical and histopathological association, but in many cases, this approach does not provide a confident diagnosis. The achievement of clinical and laboratory studies may help to understand the pathogenesis of these diseases and refine the ability to differentiate OLLs. Thus, the specific objectives of this study were: (1) conduct a systematic review of CUS with particular emphasis on clinical, histopathological and immunopathological of this newly described condition; and (2) Conducting a prospective study to evaluate the clinical and histopathological characteristics of OLLs.

O conceito de reação liquenóide ou interface liquenóide foi introduzido na dermatologia para definir diversas doenças inflamatórias da pele que apresentam características histopatológicas similares. Assim como a pele, a mucosa oral é afetada por uma variedade de lesões liquenóides orais (LLOs). As LLOs foram classificadas em: lesão liquenóide de contato; lesão liquenóide a medicamento; doença do enxerto-versus-hospedeiro e lesões liquenóides não classificáveis de aspecto liquen plano-like, como a estomatite ulcerativa crônica (EUC) recentemente descrita. Além da sobreposição de características entres as lesões que compõem este grupo, o líquen plano oral (LPO) representa o principal diagnóstico diferencial. Tradicionalmente, o diagnóstico das LLOs e do LPO depende da associação clínica e histopatológica, mas em vários casos, esta abordagem não oferece um diagnóstico confiável. As realizações de estudos clínicos e laboratoriais podem auxiliar no entendimento da etiopatogenia destas doenças e refinar a capacidade de diferenciar as LLOs. Diante disto, os objetivos específicos deste estudo foram: (1) Realizar uma revisão sistemática sobre EUC com ênfase específica nas características clínicas, histopatológicas e imunopatológicas desta condição recentemente descrita; e (2) Realizar um estudo prospectivo para avaliar as características clínicas e histopatológicas das LLOs.
Analysis of clinical features, histopathological and immunohistochemical pathological oral lichenoid lesions. Systematic review and prospective study
Keywords: Autoimmune disease; Stomatitis; Hydroxychloroquine; Doenças autoimunes; Estomatite; Hidroxicloroquina